Pd/CuO–Ni(OH)2/C as a highly efficient and stable catalyst for the electrocatalytic oxidation of ethanol. Issue 6 (16th February 2022) - Zhang, Sifan; Pei, An; Li, Guang; Zhu, Lihua; Li, Guoda; Wu, Fengshun; Lin, Shuting; Chen, Wenqi; Chen, Bing Hui; Luque, Rafael
Abstract : Pd/CuO-Ni(OH)2 /C showed superior electrocatalytic performance for EOR in comparison with PdCuNi alloy/C and Pd/C. In-situ FTIR studies have shown that CuO and Ni(OH)2 effectively inhibited the adsorption of CO and increased the breaking rate of C-C. Abstract : A novel-Pd/CuO–Ni(OH)2 /C catalyst utilizing carbon black as a support was successfully synthesized using hydrazine hydrate reduction and galvanic replacement strategies and was subsequently tested for activity in the electrocatalytic oxidation of ethanol. The observed peak current density (3.74 A mgPd −1 ) for Pd/CuO–Ni(OH)2 /C was 19.68 times higher than that of commercial Pd/C (0.19 A mgPd −1 ). The as-synthesized Pd/CuO–Ni(OH)2 /C (hereafter denoted as PdCuNi/C) catalyst exhibited a significantly improved electrocatalytic activity and durability compared with Pd/C, PdNi/C, PdCu/C and the PdCuNi/C catalysts reduced in N2 /H2 at different temperatures. The reason for this is that the high dispersion of Pd resulted in the exposure of more active sites on the surface of the catalyst. The excellent CO2 selectivity of Pd/CuO–Ni(OH)2 /C (22.5%) for the ethanol electronic oxidation reaction (EOR) was observed using in situ Fourier transform infrared spectroscopy (FTIR) spectra and could be attributed to the synergistic effect of Pd, CuO and Ni(OH)2 and the presence of the OHad adsorption at Ni(OH)2 at a low potential.